DEVELOPING LEARNING MATERIALS BASED ON TRAINING WITHIN INDUSTRY (TWI) TO IMPROVE THE BUILDING CONSTRUCTION STUDENT’S LEARNING OUTCOMES - Sugiyanto Sugiyanto; Made Wena; Isnandar Isnandar (Universitas Negeri Malang, 2018)
Abstract: Developing Learning Materials Based on Training Within Industry (TWI) to Improve the Building Construction Student’s Learning Outcomes.This second study aims to test significances differences between (1) using teaching materials with TWI method and the conventional method; (2) the high achievement motivation students and the low achievement motivation students; and (3) learning structures (TWI method and conventional method) and the high achievement motivation and the low achievement motivation toward the students’ learning outcomes. This study is an experimental research for students who take the Bricklaying and Concrete Practice lesson in an academic year. The hypothesis test uses two-way variance analysis (ANAVA) to find out the differences in the mean between cells (A and B). The results showed that there were significant differences in the students’ learning outcome between (1) the TWI teaching materials and conventional method; (2) the students who have the high achievement motivation and the students who have the low achievement motivation. Furthermore, there were significant interactions between factor of giving the vocational work practices and motivation toward the students’ learning outcomes.